Scaling up of poly (3-hydroxybutyrate) production from oil palm frond juice by Cupriavidus necator (CCUG52238T) - Mior Ahmad Khushairi, Mohd Zahari (2013)
It has been reported that oil palm frond juice (OPF) can be used as the sole renewable, alternative and cheap carbon source for the production of poly(3- hydroxybutyrate), P(3HB) at lab scale study. In order to further investigate the potential of OPF juice for P(3HB) production at larger scale, we scaled up the fermentation process from 500 ml shake flask to 20 L bioreactor based on constant volumetric mass transfer coefficient (kLa) of oxygen at both scale. It was interesting to note that the P(3HB) content obtained in this study was almost similar as reported in the previous study both in shake flask and 2 L bioreactor. The P(3HB) content for shake flask fermentation was 45 wt.%, while 44 wt.% and 42 wt.% in 2 L and 20 L bioreactor respectively. Based on the current finding, it can be concluded that the scaling up method based on constant kLa was successful due to the almost similar P(3HB) content obtained in shake flask and bioreactor scale. Overall, it can be postulated that OPF juice can be successfully used as a non-food fermentation feedstock for the production of P(3HB) both in small and large scale fermentation.